Agreement on a European Economic Area. - NORBERG, Sven (1992)
Focuses on the institutional provisions of the Agreement on a European Economic Area (EEA). Points out four common EC policies are missing in the EEA, viz. the EEA has no common external trade policy; it is a fundamentally improved free trade area but not a customs union; there are no common policies in the areas of agriculture and fishing; and, there is no common policy on taxation.